IMPLEMENTASI STANDAR PROSES PENDIDIKAN KURIKULUM MERDEKA PADA PEMBELAJARAN BAHASA INDONESIA DI SMP AL-IRSYAD KOTA JAMBI - Yuanda Safriani; Urip Sulistyo; Sophia Rahmawati (STKIP Subang, 2026)
This study aims to describe the planning, implementation, and assessment of the Independent Curriculum learning process by Indonesian language teachers at Al-Irsyad Junior High School in Jambi City. This study uses a descriptive approach with qualitative research. Two types of data are used: (1) primary data, namely observations of teaching modules, learning implementation, and interviews observing classroom learning implementation; and (2) secondary data, namely the Indonesian language teacher's teaching module and the results of open-ended interviews. Data collection techniques used were document study, interviews, observation, and recording techniques. The results of the study indicate: 1) The planning of the learning process carried out by teachers successfully implemented all the standard learning process indicators as stipulated in Minister of Education and Culture Regulation Number 16 of 2022. 2) During the implementation of the learning process, teachers were not able to fully implement the indicators for each element. Although some elements were implemented, they were not included in the teaching module. 3) Assessment of the learning process was not conducted through reflection among fellow educators but solely by the principal.